Exploring the Potential for Learning Mathematics at the Geger Hanjuang Inscription Site Through Outing Class Activities - Rizqy Amelia Putri; Mega Nur Prabawati; Eko Yulianto (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2026)
This study aims to analyze how problem posing based on the Geger Hanjuang Inscription artifacts elicits Bishop's six activities and to identify the types of mathematical ideas generated by students. The learning intervention was carried out through outing class activities, where students observed the inscription artifacts, conducted measurements and sketches, formulated mathematical questions based on their findings, and solved the problems posed. Using a descriptive and exploratory qualitative research design, this study examined how students interacted with cultural artifacts and processed them into meaningful mathematical ideas. Data were collected through observations, field notes, documentation, and student work, then analyzed using Bishop's six mathematical activities framework. Furthermore, the researcher triangulated sources to validate the validity of the data. The research findings indicate that cultural artifact-based learning has the potential to facilitate the emergence of various mathematical activities in students in contextual learning contexts such as measuring, designing, calculating, allocating, and explaining. Through tasks based on local culture, students demonstrated increased curiosity, contextual reasoning skills, and the ability to formulate mathematical problems independently. This study contributes by demonstrating the integration of ethnomathematics, problem posing and direct experience-based learning at cultural sites as a strategy to elicit students' mathematical activities.